Regulation of “Bilik Asmara” in Indonesian Correctional Institutions Between Human Rights and Security - Syam, Elvi Susanti; Hartawati, Andi; Purwanda, Sunardi (PT. Anagata Sembagi Education, 2025)
The arrangement of conjugal visits or